Scanning electron-microscopic study on subcommissural organ and pineal gland of the sheep (Ovis aries) - SAGGAR, DEEPA; KUMAR, PAWAN; KUMAR, SURAJ (The Indian Journal of Animal Sciences, 2014)
The scanning electron microscopy of the subcommissural organ of sheep revealed apical spherical protrusions and ciliary network. Cilia emerged from these protrusions and intermixed with others. Smooth surfaced spherical protrusions marked the presence of non-ciliated cells. The secretions of the subcommissural organ along with RBCs and cell debris constituted Reissner's fibre, which extended throughout the ventricular surface of the organ. The surface of the pineal gland showed a meshwork of fibrous strands, whereas, gland's cut surface demonstrated pinealocytes, glial cells and fibres.